Impact of modality and mode of questioning and testing on memory reports - Riggenbach, Mackenzie R.; Gronlund, Scott D.; Zoladz, Phillip R. (Frontiers in Cognition, 2024)
Individuals’ memories are assessed in multiple contexts; however, depending on the context, how an individual is questioned may impact the quantity and quality of the details reported. One goal of this study is to investigate how the modality of questioning (individuals talk or write about an event) impacts memory reports. Additionally, being tested on previously learned information improves memory for that information compared to re-studying it. Consequently, another goal is to examine how questioning impacts memory reports compared to a second exposure. We utilized open-ended and pointed questions (true and false). Participants watched a short video and were questioned (Experiment 1: In-Person; Experiment 2: Virtual) about its contents immediately, one week, and one month later. The current study found that writing leads to better quality memory reports than speaking, and the benefit is present one week later. Additionally, we found that writing mitigates an anticipated testing benefit, although this depended on whether a pointed or open-ended question was asked. Restudying (versus immediate testing) led to better performance for the false pointed questions. However, the better performance operated differently depending on whether participants wrote or spoke following restudying, perhaps due to a differential criterion shift between the Restudy-Written and the Restudy-Spoken conditions. We conclude that the impact of the modality of questioning is influenced in several ways by the types of questions asked, which bears significance for many domains because one modality (or a combination) may be more suitable for producing more accurate memory reports as a function of different domains.